The Perception of Special Education Teachers for Implementing STEAM Education for Students with Intellectual Disabilities (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to investigate the current perception of educational practice as special education teacher, STEAM education as an alternative approach to the traditional teaching, and the difficulties or barriers for implementing STEAM education effectively. For the purpose of this study, qualitative research design was used and continuous comparative analysis was used for the data analysis. Among teachers of special schools with intellectual disabilities, teachers who are conducting STEAM education were selected by purposive sampling. The results of this study are as follows. Special teachers have different perceptions of STEAM education. Most special teachers were positively thinking about conducting the STEAM class for students. They recognized that it could be an opportunity for students with intellectual disabilities to naturally interact with each other during class activities and to express creativity through the process of creating something by themselves. Some teachers think that STEAM classes are good, but a great deal of effort and time should be invested compared to traditional teaching methods. They felt that they lacked conceptual knowledge for conducting STEAM class in actually planning STEAM class and a lot of time and effort should be invested in preparing the class. In conclusion, special teachers were positively thinking about conducting the STEAM class for students with intellectual disabilities, but they still feel a lot of difficulties in actual implementation, thus it is necessary to provide support needed in order to activate the STEAM class.